A Strategy for Bone Conduction Device Adoption: Study of Non-Usage Challenges, Skin-Deep Insights and Patient Satisfaction - Jasmine Van de Kerkhof; Lore Bleyaert; Nicolas Verhaert; Bob Lerut (Journal of International Advanced Otology)
Background: This study aimed to evaluate patient satisfaction and usage patterns of bone conduction devices (BCDs) for hearing rehabilitation, focusing on both users and non-users. Specific objectives included assessing reasons for non-use, exploring patient perceptions of BCD efficacy, and examining complications associated with BCD implantation.